OPTIMALISASI POTENSI LOKAL (TOMAT CAKE) UNTUK PENINGKATAN EKONOMI MASYARAKAT BATUBINTANG, BATUMARMAR, PAMEKASAN BINTANG - Abd Rosyid; Moh Dannur; Moh Hafidurrahman (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAI Al-Khiarat Pamekasan, 2021)
This Community Service Assistance Activity aims to provide knowledge and information to the people of Batu Bintang Village, Batumarmar District, Pamekasan Regency, especially Micro, Small and Medium Enterprises / home businesses.regarding the use of tomatoes into cakes which are processed into various forms of attractive and delicious cakes, this Community Service is carried out by counseling or training on how to make a cake made from tomatoes and showing cake products processed from tomatoes, presentations and direct practice of how to use tomatoes to one of the cake products, then presenting and showing proper packaging according to packaging standards. Community Service activities were undertaken at the Village Hall or at muslimatan village of Batu stars Subdistrict Batumarmar Pamekasan. The willingness and active participation of the community during the process is very high. This is shown by the enthusiasm of the people who want to be given the opportunity to carry out the process of using tomatoes into processed products, namely tomato cake. The conclusion of this Community Service assistance activity is strongly supported by the community and village heads, who in the future will use tomatoes as one of the main ingredients for making cakes and as a solution to overcome the improvement of the community's economic conditions